Analisis Tingkat Pemahaman Peserta Pelatihan Budidaya Maggot Melalui Pendekatan Kuesioner - Desniwati Zai; Karya Haga Mendrofa; Julilis Suganda Mendrofa; Nisayangin Mariana Daeli; Sertifikat Waruwu; Betzy Victor Telaumbanua (Lembaga Pengembangan Kinerja Dosen, 2025)
Organic waste management is a serious challenge faced by rural communities, including in Lologolu Village, Mandrehe Sub-district, West Nias Regency. Cultivation of maggot, especially Black Soldier Fly (BSF) larvae, is one of the innovative solutions in reducing organic waste while increasing the economic value of the community. This study aims to analyze the participants' level of understanding of the maggot cultivation training material implemented by the Student Creativity Program (PKM) students through a questionnaire approach. The research used a quantitative descriptive method with 29 respondents who participated in the training. Data were collected through a five-point Likert scale questionnaire consisting of 10 statements related to material understanding and practical readiness. The results of the analysis showed that the majority of participants stated that the material was delivered clearly, interactively, and according to field needs. Most also expressed satisfaction with the activities and showed high interest in implementing maggot cultivation independently. However, there were a small number of participants who showed a neutral response or were not ready to practice directly. This finding confirms the importance of follow-up mentoring strategies to optimize the impact of the training. Overall, the training succeeded in increasing community literacy in maggot-based waste management and encouraging active participation in the application of local technology.